2008
DOI: 10.1029/2007jc004468
|View full text |Cite
|
Sign up to set email alerts
|

Waves plus currents at a right angle: The rippled bed case

Abstract: [1] The present paper deals with wave plus current flow over a fixed rippled bed. More precisely, modifications of the current profiles due to the superimposition of orthogonal cylindrical waves have been investigated experimentally. Since the experimental setup permitted only the wave dominated regime to be investigated (i.e., the regime where orbital velocity is larger than current velocity), also a numerical k-e turbulence closure model has been developed in order to study a wider range of parameters, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 30 publications
(65 reference statements)
6
29
0
Order By: Relevance
“…The bedform dimensions were chosen in such a way as to be in agreement with the characteristics of ripples generated during the experimental campaign performed by Andersen and Faraci (2003), in the presence of orthogonally superimposed waves and currents characterized by the same ratio between current velocity and wave orbital velocity. In particular it was found that the chosen bed form characteristics are typical for waves with periods between 1 and 1.4 s and heights of about 0.1 m propagating over a depth of about 0.3 m. The detailed experimental data of the RB campaign have been reported in Faraci et al (2008).…”
Section: Experimental Set Up and Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…The bedform dimensions were chosen in such a way as to be in agreement with the characteristics of ripples generated during the experimental campaign performed by Andersen and Faraci (2003), in the presence of orthogonally superimposed waves and currents characterized by the same ratio between current velocity and wave orbital velocity. In particular it was found that the chosen bed form characteristics are typical for waves with periods between 1 and 1.4 s and heights of about 0.1 m propagating over a depth of about 0.3 m. The detailed experimental data of the RB campaign have been reported in Faraci et al (2008).…”
Section: Experimental Set Up and Proceduresmentioning
confidence: 99%
“…Opposite the wavemaker a porous plane beach limits the reflection to about 10% of the incident wave. For a detailed description please refer to Faraci et al (2008) or Faraci, Foti, Marini, and Scandura (2012).…”
Section: Experimental Set Up and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations